Blood microvessel density, lymphatic microvessel density and lymphatic invasion in predicting melanoma metastases: systematic review and meta‐analysis. (January 2014) - Pastushenko, I.; Vermeulen, P.B.; Carapeto, F.J.; Van den Eynden, G.; Rutten, A.; Ara, M.; Dirix, L.Y.; Van Laere, S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Both angiogenesis and lymphangiogenesis have been recognized as crucial processes in tumour growth and metastasis development. In the last two decades, large numbers of studies evaluating microvessel and lymphatic vessel density in melanoma have been published, many of them reporting contradictory results. What does this study add? We performed a systematic review of all published data, followed by meta‐analysis, permitting a global evaluation of the existing evidence on the prognostic value of these parameters in melanoma.